Hypospadias in buffalo (Bubalus bubalis) mediterranean breed-case report - Volpato, Rodrigo [UNESP]; Araujo, Michelle Silva [UNESP]; Vexenat, Stephane Cássia Oliveira Rosa [UNESP]; Oba, Eunice [UNESP] (Lifescience Global, 2013)
Hypospadias is a rare congenital condition characterized by abnormal development of the penile urethra, penis, scrotum and prepuce. The etiopathogenesis is still not fully elucidated, but it is based on a deficiency of testosterone during the critical stage of morphogenesis. At UNESP’s experimental farm was born a Mediterranean breed buffalo calf with congenital abnormalities in the reproductive system, being diagnosed with hypospadias.
Keywords: Buffalo; Pathology; Reproductive system; Male; Hypospadias